2021
DOI: 10.1021/acs.jpcc.1c07740
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lead:Halide Precursor Ratio on the Photoluminescence and Carrier Dynamics of Violet- and Blue-Emitting Lead Halide Perovskite Nanocrystals

Abstract: Highly luminescent cesium lead halide (CsPbX 3 , X = Cl, Br, I) perovskite nanocrystals (NCs) are promising materials for a number of optoelectronic applications like LEDs and other display technologies. However, low photoluminescence (PL) quantum yield (QY) of the large-bandgap violet-and blue-emitting CsPbCl 3 and CsPb(Cl/Br) 3 NCs is an obstacle to the development of blue-and white-emitting LEDs. In this work, we show that these NCs with high PLQY can be obtained directly by employing an appropriate halide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…S6G†) is quite remarkable as it represents one of the highest reported values for this system obtained by any direct method of synthesis (Table S2†). 6,24,25,32 An important point to note here is that a stoichiometric amount of DCDMH produces these brightly luminescent CsPbCl 3 NCs (Table S2†), unlike earlier cases, where a much higher amount of chloride precursor was necessary. 6,24,25,32 We found that an excess amount of DCDMH did not have much influence on the PLQY of the system initially, but the PLQY dropped for Pb : Cl precursor ratios exceeding 1 : 7 (Fig.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…S6G†) is quite remarkable as it represents one of the highest reported values for this system obtained by any direct method of synthesis (Table S2†). 6,24,25,32 An important point to note here is that a stoichiometric amount of DCDMH produces these brightly luminescent CsPbCl 3 NCs (Table S2†), unlike earlier cases, where a much higher amount of chloride precursor was necessary. 6,24,25,32 We found that an excess amount of DCDMH did not have much influence on the PLQY of the system initially, but the PLQY dropped for Pb : Cl precursor ratios exceeding 1 : 7 (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…The shortest and major component (0.47 ns, 76%) is due to the rapid non-radiative relaxation of the carriers through the trap states. 25,37 The absence of this trapping component for the CsPbBr 3 NCs explains its higher PLQY compared to the CsPbCl 3 NCs. The calculated radiative ( k r ) and non-radiative ( k nr ) rate constants of the systems give further insight into the charge carrier recombination processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the trap states are deep in nature in violet-emitting CsPbCl 3 and blue-emitting CsPb(Cl/ Br) 3 NCs and the PLQY of these systems are typically < 5% and < 40%, respectively. [15][16][17] It is quite challenging to produce brightly luminescent blue-emitting NCs with near-unity PLQY. The literature suggests that post-synthetic surface modification is an effective way of eliminating excess lead from the surface [5,[18][19][20] and suppressing halide deficiency related defects.…”
Section: Introductionmentioning
confidence: 99%
“…An important point to note here is that as these trap states are shallow in nature in green‐ emitting CsPbBr 3 NCs, these systems possess fairly high PLQY (typically, ∼50–80%). In contrast, the trap states are deep in nature in violet‐emitting CsPbCl 3 and blue‐emitting CsPb(Cl/Br) 3 NCs and the PLQY of these systems are typically <5% and <40%, respectively [15–17] . It is quite challenging to produce brightly luminescent blue‐emitting NCs with near‐unity PLQY.…”
Section: Introductionmentioning
confidence: 99%